Infantile haemangioma expresses embryonic stem cell markers. Issue 5 (23rd March 2012) - Itinteang, Tinte; Tan, Swee T; Brasch, Helen D; Steel, Ryan; Best, Heather A; Vishvanath, Anasuya; Jia, Jun; Day, Darren J
Abstract : Background: The origin of infantile haemangioma (IH) remains enigmatic. A primitive mesodermal phenotype origin of IH with the ability to differentiate down erythropoietic and terminal mesenchymal lineages has recently been demonstrated. Aims: To investigate the expression of human embryonic stem cell (hESC) markers in IH and to determine whether IH-derived cells have the functional capacity to form teratoma in vivo . Methods: Immunohistochemical staining and quantitative reverse transcription PCR were used to investigate the expression of hESC markers in IH biopsies. The ability of cells derived from proliferating IH to form teratomas in a mouse xenograft model was investigated. Results: The hESC markers, Oct-4, STAT-3 and stage-specific embryonic antigen 4 were collectively expressed on the endothelium of proliferating IH lesions, whereas Nanog was not. Nanog was expressed by cells in the interstitium and these cells did not express Oct-4, stage-specific embryonic antigen 4 or STAT-3. Proliferating IH-derived cells were unable to form teratomas in severely compromised immunodeficient/non-obese diabetic mice. Conclusion: The novel expression of hESC on two different populations of cells in proliferating IH and their inability to form teratomas in vivo infer the presence of a primitive cellular origin for IH downstream from hESC.